2020
DOI: 10.1038/s41419-020-03009-4
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoids induce differentiation and chemoresistance in ovarian cancer by promoting ROR1-mediated stemness

Abstract: Glucocorticoids are routinely used in the clinic as anti-inflammatory and immunosuppressive agents as well as adjuvants during cancer treatment to mitigate the undesirable side effects of chemotherapy. However, recent studies have indicated that glucocorticoids may negatively impact the efficacy of chemotherapy by promoting tumor cell survival, heterogeneity, and metastasis. Here, we show that dexamethasone induces upregulation of ROR1 expression in ovarian cancer (OC), including platinum-resistant OC. Increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 48 publications
4
34
2
Order By: Relevance
“…ROR1, in turn, supported tumor colonization and metastasis formation at these sites [ 109 ]. Similar observations have been made in ovarian cancer, in which the synthetic glucocorticoid dexamethasone induced ROR1 expression, which correlated with elevated RHOA, YAP/TAZ, and BMI-1 levels in a panel of ovarian cancer cell lines as well as in the primary patient-derived cells [ 167 ]. As both YAP/TAZ and BMI-1 regulate the differentiation and self-renewing capacity of cancer stem cells, these observations could provide the molecular basis underlying the ROR1-associated stemness phenotype.…”
Section: Wnt/ror Signaling At a Glancesupporting
confidence: 74%
“…ROR1, in turn, supported tumor colonization and metastasis formation at these sites [ 109 ]. Similar observations have been made in ovarian cancer, in which the synthetic glucocorticoid dexamethasone induced ROR1 expression, which correlated with elevated RHOA, YAP/TAZ, and BMI-1 levels in a panel of ovarian cancer cell lines as well as in the primary patient-derived cells [ 167 ]. As both YAP/TAZ and BMI-1 regulate the differentiation and self-renewing capacity of cancer stem cells, these observations could provide the molecular basis underlying the ROR1-associated stemness phenotype.…”
Section: Wnt/ror Signaling At a Glancesupporting
confidence: 74%
“…The relevance of ROR1 and its therapeutic role has been recently explored in ovarian cancer. Indeed, it has been demonstrated that ROR1 has an important therapeutic role in such a neoplastic disease because glucocorticoids anti-inflammatory agents (generally administred as adjuvant to chemotherapy) may induce chemoresistance by promoting ROR1-mediated stemness [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that in gynaecological cancer, GR expression increases risk of death or progression by 68% and 83%, respectively ( Figure 3 and Figure 4 ). Indeed, GR signalling has been shown to negatively impact ovarian cancer disease outcomes by promoting ROR-1 induced stemness and inducing taxane resistance, a mainstay of ovarian cancer treatment [ 67 ]. Moreover, addition of GR antagonists to chemotherapy regimens has improved response in patient derived xenograft PDX models of ovarian cancers and they are in development for endometrioid cancer [ 68 , 69 ].…”
Section: Discussionmentioning
confidence: 99%